Neonatal and clinical outcomes after transfer of a mosaic embryo identified by preimplantation genetic testing for aneuploidies. Issue 1 (July 2022) - Yakovlev, Pavel; Vyatkina, Svetlana; Polyakov, Alex; Pavlova, Marina; Volkomorov, Victor; Yakovlev, Maksim; Filimonov, Sergey; Kazaryn, Liya; Aizikovich, Asia; Kornilov, Nikolay
Abstract: Research question: Do clinical and neonatal outcomes differ between mosaic embryo transfers (MET) and euploid embryo transfers (EET)? Design: This retrospective cohort study compared the implantation rate, live birth rate (LBR) and miscarriage rate between 513 euploid embryos and 118 mosaic embryos (72 whole chromosome mosaic [WCM], 40 segmental mosaic and six complex mosaic). Blastocysts were analysed using preimplantation genetic testing for aneuploidies with next-generation sequencing, followed by a single vitrified-warmed embryo transfer. Trophectoderm biopsies were classified as mosaic if they had 20–80% abnormal cells. Results: Overall, EET resulted in a significantly higher implantation rate (47.0%) and LBR (40.7%) than MET (implantation rate 39.0%, P = 0.005; LBR 28.8%, P = 0.008) and WCM embryos (implantation rate 37.5%, P = 0.01; LBR 22.2%, P = 0.007) after covariate adjustment. Segmental mosaic embryos had an implantation rate (47.5%) and LBR (45.0%) comparable to those of euploid embryos. Mosaic embryos with a high percentage of aneuploid cells (≥60%) showed a significantly lower LBR (10.5% versus 40.7%, P = 0.03) than euploid embryos after covariate adjustment, with three of the five implantations of mosaic embryos resulting in miscarriage. Neonatal outcomes did not differ significantly between the mosaic and euploid groups. Of the 34 women with a live birth after MET, 13 had a prenatal or postnatal genetic testing result, and no abnormalities were found. Conclusions: Mosaic embryos were associated with a lower LBR, while segmental mosaic embryos had similar clinical outcomes to euploid embryos. Mosaic embryos with a high aneuploidy percentage (≥60%) should be assigned a low transfer priority. Neonatal outcomes did not differ significantly between the euploid and mosaic groups.